2012
DOI: 10.1002/nme.4327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic failure simulation of quasi‐brittle material in dual particle dynamics

Abstract: The feasibility of simulating dynamic fracture in quasi-brittle material using a dual particle computational method with a smeared-crack representation of material failure is explored. The computational approach utilized is dual particle dynamics, which incorporates a moving least squares interpolation of field variables between two sets of particles that discretize the spatial domain, and a Lagrangian description of the moving least squares weight function. Material failure is represented by an inelastic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…the discrete residuals are strictly zero when evaluated at the primary set of particles). Hence, and taking inspiration from the Dual Particle Method, [25,[53][54][55], a secondary set of particles is employed in order to account for the effect of these SUPG terms.…”
Section: Supg Contributionmentioning
confidence: 99%
“…the discrete residuals are strictly zero when evaluated at the primary set of particles). Hence, and taking inspiration from the Dual Particle Method, [25,[53][54][55], a secondary set of particles is employed in order to account for the effect of these SUPG terms.…”
Section: Supg Contributionmentioning
confidence: 99%
“…Use of Equations (15), (33), and (34) result in the following decoupled equations for stress at a boundary particle.…”
Section: Traction Boundary Conditionsmentioning
confidence: 99%
“…It has been shown that use of a Lagrangian SPH approximating function precludes some instabilities altogether [26][27][28][29]. Dual particle dynamics (DPD) [30][31][32][33], a particle method developed for dynamic problems in solids, incorporates a Lagrangian description of the MLS approximation of quantities and their spatial derivatives, as well as a two particle set discretization of the solid continuum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another most popular meshless methods are the element‐free Galerkin method , the reproducing kernel particle method , and the meshless local Petrov–Galerkin method . A number of different meshless methods have been developed in recent years, and a good review on meshless methods and their implementation can be found in literature (e.g., ).…”
Section: Introductionmentioning
confidence: 99%